Narrative Form and Chaos Theory in Sterne, Proust, Woolf, and Faulkner - Parker, J. author. aut Link
XVI, 187 p.
Keywords: Drawing on the insights offered by contemporary chaos theory, Narrative Form and Chaos Theory explores how models of turbulent dynamical systems in the physical world parallel structures in certain kinds of narratives. By closely looking at Laurence Sterne's Tristram Shandy, Marcel Proust's In Search of Lost Time, Virginia Woolf's Mrs. Dalloway, and William Faulkner's Absalom, Absalom!, Parker demonstrates how these insights can be applied to the analysis of narrative structure and meaning. This innovative interdisciplinary work will appeal to scholars interested in narratology and in the connection between chaos theory and literature.